New records of Pseudophatnoma laosana B. Lis, 1999 (Hemiptera: Tingoidea: Cantacaderidae) from China and Thailand, with illustration of its male genitalia - Lis, Barbara; Dang, Kai; Bu, Wenjun (Zootaxa, 2015)
The lace-bug genus Pseudophatnoma was described for P. corniculata from the Riau Archipelago in Indonesia, and because of its morphological characteristics the genus was placed in the subfamily Cantacaderinae of the family Tingidae (Blöte 1945).